Sonographic Mapping of the Normal Brachial Plexus - Demondion, Xavier; Herbinet, Pascal; Boutry, Nathalie; Fontaine, Christian; Francke, Jean-Paul; Cotten, Anne (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Mapping of the brachial plexus with MR imaging has been reported and may have potential clinical applications (eg, precise localization of traumatic or tumoral nerve lesions, selective anesthesia of the brachial plexus). We sought to demonstrate that mapping of the brachial plexus may be performed by means of sonography.METHODS: Twelve healthy adult volunteers (seven women and five men; age range, 24–38 years; mean, 31 years) underwent bilateral sonographic examination for the assessment of the nerve structures of the brachial plexus from the extraforaminal part to the axillary part. Four formolated cadavers (two male and two female; age range, 66–84 years; mean, 77.5 years) were frozen and sawed into 3-mm-thick contiguous sections in the same plane as that used for the sonographic exploration.RESULTS: A satisfactory sonographic examination was performed in 10 of 12 volunteers, leading to a good association with anatomic sections. Two volunteers were excluded from the study because a clear depiction of the brachial plexus was difficult owing to a short neck and low echogenicity at examination. The association between sonographic images and anatomic sections allowed us to map the brachial plexus. The subclavian and deep cervical arteries were useful landmarks for this mapping. The eighth cervical nerve root and the first thoracic nerve root were the most difficult part of the brachial plexus to depict because of their deep location.CONCLUSION: The brachial plexus can be mapped with sonography. However, this technique requires a good grounding in anatomy and may be impossible in short-necked individuals.